The Nature of Pandemics in the perspective of Christian Theology - Muhammad Zia ul Haq; Muhammad Riaz Mehmood (jihat-ul-islam, 2021)
Religious literature and its interpretations have a significant role in the studies of the nature and history of different pandemics. The present study aims to discuss the view point of Christianity about pandemic situations. It also tries to analyze the perceptions about the pandemics in different Christian theological perspectives. The Bible has mentioned a number of pandemics as heavenly whips and the Bani Israel adopted the method of quarantine to avoid their spread. The quarantine period ranged from seven days for some diseases to indefinite period for others. According to the teachings of Christianity, God is the Superior Being and it is imperative for human beings to have complete faith in Him in all kinds of circumstances. He has the power to eliminate all kinds of disasters, including epidemics and pandemics and does not cause human sufferings unnecessarily. However, it is not correct to say that every pandemic is the result of human sins and faults. In fact, God’s wisdom may sometimes not be understandable to human beings. Satan can inflict pandemics on people, but he cannot go beyond the limits set by God. There are several reasons for the outbreak of pandemics as per Christian thought: sometimes they are a punishment for people’s sins; sometimes they are just a warning, sometimes they are a sign for moving towards the Day of Judgment and sometimes they are a test of human perseverance. They provide an opportunity to man to improve his relationship with God through forgiveness, repentance, hope and reformation. Sometimes, they offer a stimulus for the awakening of faith. For Christians, there is no issue in agreeing to any or all of these options. It is reassuring to know that God 96 has not left human beings alone and helpless in such a situation, but has provided valuable guidance in the form of His teachings.